Linking bank competition, financial stability, and economic growth - Ijaz, Shahzad; Hassan, Arshad; Tarazi, Amine; Fraz, Ahmad (Journal of Business Economics and Management, 2020)
This paper investigates the effect of bank competition and financial stability on economic growth by examining panel-data from 38 European countries over 2001 to 2017. Bank competition is measured with the Boone indicator, and bank stability with Z-scores and non-performing loan ratios, all at the country level. This study employs a fixed-effect estimator, as well as a system generalized method of moment (GMM) estimator to control unobserved heterogeneity, endogeneity, the dynamic effect of economic growth, and reverse causality in its estimation. Results show that bank stability significantly contributes to economic growth in Europe. Economic growth falls during crisis periods (both the global financial crisis and the local banking crisis), highlighting the importance of a resilient banking system during crisis periods. Moreover, empirical outcomes show that lower banking competition supports economic growth and increases financial stability. This study provides a framework for banks and regulators to boost economic growth through the channel of banking stability.